Corporate Governance and Its Effect On Firm Performance In An Emerging Economy - KAREM, Langa Esmael; HAMAD, Hawkar Anwer; BAYZ, Hakar Abubakir; FATAH, Naji Afrasyaw; ALI, Diary Jalal; AHMED, Znar Nahro; GARDI, Bayar; QADER, Khowanas Saeed (International Journal of Environmental, Sustainability, and Social Science, 2021)
Having a board of directors is very important to ensure the smooth running of business processes and have an impact on the company's financial performance. This study to determine the impact of board characteristics namely board size, board ownership and board composition on the financial performance of organizations as measured by Return on Assets. The study employed a descriptive-explanatory research design based on a cross-sectional approach. Correlation and regression analyses were conducted to determine the depth and extent of the relationship between the variables. The study revealed a positive and significant association between the board size and financial performance on an average of 9 board members. Board composition revealed that having more external directors had no effect on the financial performance, it neither increased it nor decreased it, leading to the rejection of the hypothesis. On the other hand, board ownership was found to be beneficial in terms of having directors as owners of the business, corroborating the Stakeholder Theory. The studies showed that there was still a need to select board members with caution striking a balance between the number of directors as well as their composition to ensure that the organization reaps maximum benefits from the board.